2010
DOI: 10.1186/1471-2164-11-215
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of mountain pine beetle (Dendroctonus ponderosae) midguts and fat bodies

Abstract: BackgroundThe mountain pine beetle (Dendroctonus ponderosae) is a significant coniferous forest pest in western North America. It relies on aggregation pheromones to colonize hosts. Its three major pheromone components, trans-verbenol, exo-brevicomin, and frontalin, are thought to arise via different metabolic pathways, but the enzymes involved have not been identified or characterized. We produced ESTs from male and female midguts and associated fat bodies and used custom oligonucleotide microarrays to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Bars for larvae and pupae are shown in gray because their sex was not determined. The data in D and E have been reported previously (25).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Bars for larvae and pupae are shown in gray because their sex was not determined. The data in D and E have been reported previously (25).…”
Section: Resultsmentioning
confidence: 58%
“…In addition, an ortholog to the I. pini GPPS/MS (13) could not be found in the MPB genome (22) or in the MPB, SPB, or WPW transcriptome assemblies (NCBI TSA accession no. GAEO00000000) (25,26), reinforcing the unique role that IpinGPPS/MS plays in pheromone biosynthesis in I. pini (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6), following the action of a cleavage enzyme and an isomerase reactions as above. Both FPPS and GGPPS are up-regulated in D. ponderosae male midguts after males join females in nuptial chambers (Aw et al, 2010). 3-Another route has been proposed by Francke and Schulz (personal communication) in which 6HMO originates from isopentenyl diphosphate (IPP) by the addition of three carbons from acetoacetyl-CoA.…”
Section: Frontalinmentioning
confidence: 97%
“…The current list of activities for insect P450s characterized via one of the heterologous expression systems mentioned above is presented in [250,251] Other activities expected to be conserved among insect species include those mediating fatty acid hydroxylations; here again, it is surprising that only one ( D. melanogaster CYP6A8) has been shown to have any ability to oxygenate fatty acids [252] Other biosynthetic P450s in insects have been sporadically identified as researchers have sought to delineate species-specific conversions involved in the production of insect defense toxins and pheromones Recently characterized in Zygaena filipendulae (burnet moth) larvae, CY-P332A3 and CYP405A2 are responsible for the synthesis of the cyanogenic glycosides linamarin and lotaustralin from valine and isoleucine, respectively [253] Mediating multiple steps converting amino acids to cyanogenic glycosides, these P450s have convergently evolved the same sorts of sequential conversions used in the synthesis of dhurrin, linamarin, and lotaustralin in cyanogenic plants (sorghum, cassava, lotus) [253] Characterized in Ips paraconfusus (california fivespined ips) and Ips pini (pine engraver beetles), the CYP9T subfamily mediates both biosynthetic and detoxicative reactions in using the monoterpene myrcene present in conifer bark as the substrate for the production of aggregation pheromone [254][255][256], a mixture of ipsdienol, ipsenol, and other volatiles that recruit other beetles to damaged trees [257] And, because they cannot rely solely on the presence of plant-derived myrcene, male bark beetles are also capable of synthesizing myrcene de novo and converting it into ipsdienol and ipsenol [257] Biochemical characterizations of the species-specific differences between members of the CYP9T subfamily have shown that I. paraconfusus CYP9T1 utilizes myrcene to produce ipsdienol and ipsenol [255] and I. pini CYP9T2 and CYP9T3 (isolated from geographically distinct regions) utilize myrcene, pinene, carene, and limonene to produce ipsdienol and an array of other volatiles [254][255][256] Another enzyme implicated in pheromone production is the Dendroctonus ponderosae (mountain pine beetle) CYP6CR1, which has been suggested to mediate the male-specific fatty acid epoxidation leading to production of the pheromone exo-brevicomin and another unidentified P450 has been suggested to mediate the female-specific hydroxylation of ingested α-pinene to the pheromone verbenol [258] While the CYP15A and CYP15C subfamily members in 20-HE synthesis provide evidence that catalytic site differences can impact reaction orders in synthetic pathways, there are many more examples providing evidence that catalytic site divergences impact substrate preferences in detoxicative pathways Originating in studies to understand the ecological bases for host plant ranges and shifts in nonmodel insects, catalytic site restrictions decreasing substrate range have been n...…”
Section: P450s In Model and Nonmodel Insectsmentioning
confidence: 99%